The impact of macroeconomic indicators on carbon emission in Indonesia - Vita Kartika Sari (Program Magister Ilmu Ekonomi Pascasarjana Universitas Jambi, 2022)
The advancement of the industrial sector in economic activities can negatively impact the environment. Inefficient use of natural resources causes environmental damage in almost all countries. Environmental damage caused by economic activities becomes a crucial issue. Hence, the main purpose of this research is to estimate the impacts of macroeconomic indicators on increasing CO2 emissions in Indonesia with time-series data from 1970 to 2016. The macroeconomic indicators used in this research were broad money, foreign direct investment, value-added manufacturing, and international trade. The analysis method was ARDL-ECM (Autoregressive Distributed Lag-Error Correction Model) for long-term and short-term analysis. The main findings in the long term value-added manufacturing and international trade have positive effects on the formation of CO2 emissions. In contrast, foreign direct investments have significant but negative effects at the 10% significance level of CO2 emissions. In the short term, only value-added manufacturing and international trade variables have significantly influenced the formation of CO2 emissions in Indonesia. In contrast, foreign direct investments have been proven to be insignificant. Broad money in both the long and short term is insignificant to CO2 emissions. Based on these findings and changing climatic conditions, it is necessary to have economic development policies that reduce emissions to preserve the environment and human civilization in the long term.